2021
DOI: 10.1038/s41598-021-99751-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for intraoperative endplate injury during minimally-invasive lateral lumbar interbody fusion

Abstract: During lateral lumbar interbody fusion (LLIF), unintended intraoperative endplate injury (IEPI) can occur and thereafter lead cage subsidence. The aim of this study was to investigate the incidence of IEPI during LLIF, and its predisposing factors. A retrospective review was conducted on consecutive patients (n = 186; mean age, 70.0 ± 7.6 years) who underwent LLIF at 372 levels. Patient’s demographic and surgical data were compared between patients with and without IEPI. Also, the radiographic data of each lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The effects of osteoporosis make up a large proportion of patient factors that influence decompression. Kim et al noted that endplate injury might be affected by cortical bone strength [ 12 ]. It has been reported that the endplate cranial to the disc was thicker and of greater density than the caudal disc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of osteoporosis make up a large proportion of patient factors that influence decompression. Kim et al noted that endplate injury might be affected by cortical bone strength [ 12 ]. It has been reported that the endplate cranial to the disc was thicker and of greater density than the caudal disc.…”
Section: Discussionmentioning
confidence: 99%
“…However, these LLIF procedures can result in several perioperative complications, including nerve injury, vascular injury, or endplate injury [ 3 , 9 , 10 , 11 ]. Among these, endplate injury often occurs during endplate preparation and cage placement [ 12 ]. Once it occurs, it may result in cage subsidence to adjacent vertebral endplates, leading to the loss of segmental lordosis, foraminal height, and postoperative indirect decompression.…”
Section: Introductionmentioning
confidence: 99%
“…The results of Kanayama et al further discussed clinical symptoms following intervertebral fusion and noted that disc angle in flexion is an important prognostic factor [ 23 ]. Considering the predictive performance of sagittal DA in predicting complications after MIS-TLIF surgery at the L5-S1 level, including a higher DA suggesting a lower fusion rate of the operated segment [ 24 ] and a lower DA being a significant associated factor of intraoperative endplate injury [ 25 ] and fixed flat-back deformity [ 26 ], future studies need to develop individualized models of the corresponding vertebral segment when investigating the triggers of symptomatic ASD. In parallel, the pathological process of ASD requires to be defined precisely in order to preclude the interference of natural degeneration of adjacent vertebrae.…”
Section: Discussionmentioning
confidence: 99%
“…Unintentional intraoperative endplate injuries in XLIF have been identified in 10.4% to 20.4% of cases [ 4 , 5 ]. The vertebral endplate injuries were not correlated with surgical experience but rather with patient factors, such as older age, female gender, low bone density, preoperative disc angle, and vertebral endplate stiffening, as well as cage height [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%